A Consumer Behavior and Lifestyle with the Interest of Buying As Mediation in Determining Home Purchase with Subsidy Credit in Jember (International Journal of Scientific Research and Management (IJSRM), 2020)
The need for houses is almost never decreasing, this opportunity is exploited by developers to realize government programs related to meeting the needs of subsidized housing mortgages. Developers must be able to know how consumer tastes are changing every day in line with current trends, and it is a challenge for developers to be able to predict future demand. This understanding needs further investigation to find out how consumers consider everything before finally making a decision to buy. The purpose of this study was to analyze and determine the effect of consumer behavior and lifestyle on the interests and decisions of the purchase of subsidized KPR housing in Jember Regency. The sample in this study consumers from 10 developers in Jember were 150 respondents. The results of the analysis show that consumer behavior influences consumer buying interest in the purchase of subsidized housing mortgages, lifestyle influences consumer buying interest in home mortgages, consumer behavior influences consumer purchasing decisions in buying subsidized housing mortgages in Jember, lifestyle has a significant effect on purchasing decisions in buying subsidized housing mortgages in Jember, buying interest influences purchasing decisions in determining the purchase of subsidized housing mortgages in Jember, and based on the results of testing the direct and indirect influence of consumer behavior and lifestyle on purchasing decisions through interest, the results show that the direct influence of consumer behavior and the lifestyle of buying interest and purchasing decisions has a greater influence than indirect influence. Keywords: consumer behavior, lifestyle, buying interest and purchasing decisions.